Indonesian EFL Teachers’ Perceptions on Flipped Classroom Approach in Modern Classroom Contexts - Kristian Florensio Wijaya (Universitas Muhammadiyah Yogyakarta, 2023)
One of the notable shifts EFL educationalists have to incorporate to promote more holistic language learning outcomes is the learner-oriented approach. With this background issue in mind, flipped classroom approach is rewarding to be integrated with nowadays classroom contexts since second language learners are more capable of becoming more proactive, responsible, and well-organized learning community members. This case study was conducted to generate richer and more robust research results out of the specific research phenomenon. The main purpose of this case study is to reveal the importance of integrating flipped classroom approach in modern classroom contexts to Indonesian EFL educators. To fulfill this study objective, two experienced Indonesian EFL teachers were invited to share their experiences in utilizing flipped classroom approach by filling out five open-ended written narrative inquiry questions through the WhatsApp application. Regarding the obtained research results, there were two major specific themes namely: (1) The effectiveness of flipped classroom approach depends on learners’ learning eagerness and (2). Flipped classroom approach progressively promotes more fruitful learning outcomes. Based on these two themes, it can be fairly inferred that the constant internalization of flipped classroom approach can promote a significant degree of benefits for EFL learners’ target language learning proficiency, motivation, and independence.